(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The main idea of the presented work is to find the ways of recycling the sawing waste/sludge in production of the new concrete. The aim of the study is to examine application of the dust-water suspension as micro filler in self-compacting concrete. In the process of sawing concrete elements a lot of dust waste is produced, the average amount being approximately 0.5-1% of the total amount of concrete. To avoid dust pollution in a production plant the sawing process is accompanied by a water stream, as a result, concrete dust as dust-water suspension is stored in special reservoirs. Recycling of such concrete dust suspension and its utilization as a material pose a significant challenge.